Informing Future Land Systems Using Self-Reported Pathways and Barriers to Connections to Nature: A Case Study in Auckland, New Zealand - Fehnker L; Pearson D; Howland P (MDPI (Basel, Switzerland), 2022)
Empirical research exploring what increases an individual’s connection to nature is growing, however research seeking respondents to self-report what they feel acts as a barrier or pathway to their connection to nature is scarce. Previous empirical literature suggests a link between connections to nature and pro-nature actions. Therefore, understanding what acts as a barrier or pathway to people’s connection to nature can provide insight as to what may promote, or hinder, pro-nature actions. From a land systems perspective, the research is crucial, given that human disconnection from nature is argued to be the reason behind large scale ecological crises and species extinction which threaten the land systems in which we live. Consequently, a cross-sectional qualitative study was undertaken in 2019 with 976 respondents from Auckland, New Zealand to explore self-reported perceptions of what acts as a barrier or pathway towards their connections to nature. The findings suggest that respondents perceive modern society modalities such as ‘life takes over’, ‘urban life’, etc., as being barriers to their connections to nature. Being exposed to nature, was perceived as a pathway to prompting, and/or sustaining their connections to nature. These learnings highlight the benefit of exploring the perceived influences on connections to nature and the findings can be applied to improve the human–nature connection and therefore potentially increase pro-nature actions. We also use the findings to provide practical actions for environmental managers in the Auckland region by advising as to how the human–nature connection can be supported through future urban planning and better designed urban land systems.